Spatial collinear restricted four-body problem with repulsive Manev potential - Barrabés, Esther; Cors, Josep M.; Vidal, Claudio (Celestial mechanics and dynamical astronomy, 2017)
We outline some aspects of the dynamics of an infinitesimal mass under the Newtonian attraction of three point masses in a symmetric collinear relative equilibria configuration when a repulsive Manev potential ( - 1 / r + e / r 2 ), e > 0 , is applied to the central mass. We investigate the relative equilibria of the infinitesimal mass and their linear stability as a function of the mass parameter β , the ratio of mass of the central body to the mass of one of two remaining bodies, and e . We also prove the nonexistence of binary collisions between the central body and the infinitesimal mass.